Hybrid Sequencing Resolved Inverted Terminal Repeats in the Genome of Megavirus Baoshan - Xia, Yucheng; Cheng, Huanyu; Zhong, Jiang (Frontiers in Microbiology, 2022)
Mimivirus is a group of amoeba-infecting DNA viruses with linear double strand genome. It was found to be ubiquitous in nature worldwide. Here, we report the complete genome of a new member of Mimivirus lineage C isolated from a fresh water pond in Shanghai, China. Its 1,224,839 bp genome encoded 1,062 predicted ORFs. Combining the results of Nanopore, Illumina and Sanger sequencing technologies, two identical 23,919 bp inverted terminal repeats (ITRs) were identified at both extremities of the viral linear genome, one of which was missing in the draft assembly based on Illumina data only. The discovery of ITRs of Mimivirus provided a new insight into Mimivirus genome structure.